The Rise and Fall of Local Elections in China - Martinez-Bravo, Monica; Padró I Miquel, Gerard; Qian, Nancy; Yao, Yang (American Economic Review, 2022)
We posit that autocrats introduce local elections when their bureaucratic capacity is low. Local elections exploit citizens’ informational advantage in keeping local officials accountable, but they also weaken vertical control. As bureaucratic capacity increases, the autocrat limits the role of elected bodies to regain vertical control. We argue that these insights can explain the introduction of village elections in rural China and the subsequent erosion of village autonomy years later. We construct a novel dataset to document political reforms, policy outcomes, and de facto power for almost four decades. We find that the introduction of elections improves popular policies and weakens unpopular ones. Increases in regional government resources lead to loss of village autonomy, but less so in remote villages. These patterns are consistent with an organizational view of local elections within autocracies. (JEL D72, D73, D83, O17, O18, P25, P26)